2013
DOI: 10.4276/030802213x13679275042645
|View full text |Cite
|
Sign up to set email alerts
|

Using Museum Objects to Improve Wellbeing in Mental Health Service Users and Neurological Rehabilitation Clients

Abstract: Introduction:The study investigated the impact of museum object handling sessions on hospital clients receiving occupational therapy in neurological rehabilitation and in an older adult acute inpatient mental health service.Methods: The research used a qualitative approach based on objectivist and constructionist methods, from which themes typical of the object handling sessions were derived.Results: Themes emerging from detailed analysis of discourse involving clients (n = 82) and healthcare staff (n = 8) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 11 publications
2
47
0
Order By: Relevance
“…Thomson et al, 2012b). The act of taking an object into one's hands can be a 20 powerful experience (Samuels, 2008) particularly in the context of a hospital environment where opportunities for tactile stimulation are often minimal for long periods of time (Ander et al 2013). Activities involving touch in moulding clay have been associated with health and wellbeing benefits (Timmons & MacDonald, 2008) with participants citing touch as enriching the sessions.…”
Section: Wellbeing and Engagement Processesmentioning
confidence: 99%
See 4 more Smart Citations
“…Thomson et al, 2012b). The act of taking an object into one's hands can be a 20 powerful experience (Samuels, 2008) particularly in the context of a hospital environment where opportunities for tactile stimulation are often minimal for long periods of time (Ander et al 2013). Activities involving touch in moulding clay have been associated with health and wellbeing benefits (Timmons & MacDonald, 2008) with participants citing touch as enriching the sessions.…”
Section: Wellbeing and Engagement Processesmentioning
confidence: 99%
“…Nonetheless, the present study highlighted "learning about objects, learning from each other" as a major theme which maps onto findings in the extant literature. For example, grounded theory analysis by Ander et al (2013) cited learning new things an element of museum object handling that enhanced participants' feelings of competence and confidence. Additionally, Paddon et al (2013) reported that a large proportion of session conversation involved learning and highlighted the code "guessing game" (p. 40) closely related to "guided discovery, guessing games and questions" indicated above.…”
Section: Wellbeing and Engagement Processesmentioning
confidence: 99%
See 3 more Smart Citations